2013
DOI: 10.1111/tid.12156
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide as part of the treatment for multidrug‐resistant cytomegalovirus disease after lung transplantation: case report and review of the literature

Abstract: Treatment of cytomegalovirus (CMV) disease in transplant patients is challenging and, with antiviral resistance to first-line drugs, it remains uncertain which treatment algorithm to follow. Some data suggest that leflunomide, a pyrimidine synthesis inhibitor, can be used to treat resistant CMV infections. We report a 57-year-old CMV immunoglobulin-G (IgG)-seronegative woman, who received a bilateral lung transplant (LuTx) from a CMV IgG-positive donor with CMV primary disease. The CMV strain was genotypically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…At this point, no approved therapeutic options for CMV disease were available and unfortunately, no access to compassionate use of novel anti-CMV drugs under clinical development was available. Although a few reports have described the use of leflunomide for therapy of multidrug-resistance CMV disease (Avery et al, 2004;Levi et al, 2006;Verkaik et al, 2013;Dunn et al, 2013), treatment with this drug having both immunosuppressive and anti-CMV properties was not envisaged in our patient.…”
Section: Discussionmentioning
confidence: 92%
“…At this point, no approved therapeutic options for CMV disease were available and unfortunately, no access to compassionate use of novel anti-CMV drugs under clinical development was available. Although a few reports have described the use of leflunomide for therapy of multidrug-resistance CMV disease (Avery et al, 2004;Levi et al, 2006;Verkaik et al, 2013;Dunn et al, 2013), treatment with this drug having both immunosuppressive and anti-CMV properties was not envisaged in our patient.…”
Section: Discussionmentioning
confidence: 92%
“…Given the limited options for standard CMV antivirals, there are ongoing suggestions to use drugs that alter cellular metabolic pathways to reduce the rate of CMV replication, such as mTor inhibitors, artesunate [31] and leflunomide [32]. These adjunctive measures have had mixed success in overcoming negative host factors that contributed to the development of drug resistance, but adjusting post-transplant immunosuppression in favor of an mTor inhibitor may be practical in the absence of adverse drug interactions or other concerns [5].…”
Section: Treatment Strategies For Drug-resistant CMVmentioning
confidence: 99%
“…In vitro phenotypic assays have indicated that leflunomide is active against both wild-type and ganciclovir-resistant CMV strains, 4 and leflunomide has been used to treat CMV in a few patients. 5 In our patient, CMV PCR remained low for 2 weeks after the introduction of leflunomide, but then went up again over the next 2 weeks. The following and final decrease in CMV DNA correlated well with the concurrent development of a CMV-specific immune response.…”
Section: Discussionmentioning
confidence: 46%